1988
DOI: 10.1007/bf02239647
|View full text |Cite
|
Sign up to set email alerts
|

Clinical zinc and copper deficiencies in cattle of western Sudan

Abstract: Clinical cases of both Zn and Cu deficiencies are reported in a cattle farm in Kordofan Region of the Sudan after drought. The animals showed general weakness, stunted growth, infertility, parakeratosis and achromotrichia. There was macrocytic hypochromic anaemia and low Cu and Zn concentrations in sera. The condition was more prevalent in zebu-Friesian crosses than the local breeds. Drought and marginal or low Cu and Zn content in pasture may be the predisposing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Results of this study was compatible with Bedwal et al, (1994) who stated that zinc, copper and selenium have significant roles in maintaining good health condition in farm animals as deficiency of these trace elements in our study results in a case of calf ill-thriftiness, this also was in agreement with Damir et al, (1988) who reported that low blood copper and zinc concentrations in growing animals result in general weakness, stunted growth and anemia.…”
Section: Discussionsupporting
confidence: 92%
“…Results of this study was compatible with Bedwal et al, (1994) who stated that zinc, copper and selenium have significant roles in maintaining good health condition in farm animals as deficiency of these trace elements in our study results in a case of calf ill-thriftiness, this also was in agreement with Damir et al, (1988) who reported that low blood copper and zinc concentrations in growing animals result in general weakness, stunted growth and anemia.…”
Section: Discussionsupporting
confidence: 92%
“…Frequently, no signs of clinical copper deficiency are seen in studies with zebu cattle despite severely inadequate Cu supply based on recommended levels for B. taurus cattle (Roeder, 1980;Faye et al, 1991;Dermauw et al, 2013b). Other studies suggest that there might be a difference in response to the same diet between the local zebu cattle and B. taurus crossbred cattle (Friot, 1973;Damir et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Copper deficiency is wide spread and the pathological feature are well documented in cattle, sheep, goats and other ruminants (Underwood 1977;Mills 1983;McDowell 1985;Abu Damir et al 1988;Ivan et al 1990; Ali and Al-Noaim 1992;Hastings and Gascoyne 1992). In the camel, copper deficiency threshold was first proposed by Tartour (1975) in Western Sudan and this was confirmed by Abu Damir et al (1983) and by Faye and Bengoumi (1997).…”
Section: Introductionmentioning
confidence: 91%